Career trajectories of junior athletes in Latin America and the Caribbean and their relationship with mental health - Pons, J.; Borrueco, M.; Chamorro, J. L.; Alcaraz, S.; Espinal, D. J.; Conde, E. (International Journal of Sport and Exercise Psychology, 2025)
Career trajectories can impact athletes` mental health. There is a lack of research focusing on athletes from Latin America and the Caribbean compared to other contexts such as North America and Europe. Our study aims to characterise the career trajectories of junior athletes in Latin America and the Caribbean and examines their relationship with mental health. We recruited 236 junior high-performance athletes between 14 and 23 years (44.5% female) from Latin America and the Caribbean regions, and collected information on their career trajectories for the athlete`s tendency to prioritise a given life-sphere and their mental health using the General Health Questionnaire-12, which includes indicators of social functioning, anxiety and depression, and loss of confidence and self-esteem. Through cluster analysis, we identified distinct trajectory clusters: Sport priority (33.3%) where athletes solely prioritise sport, Dual career priority (28.9%) where athletes prioritise both sport and studies, No clear priority (9.9%) indicating no apparent priority domain, and Triple career priority (28.0%) where athletes prioritise all three life spheres. Altogether, only 56.9% of the athletes actually prioritised one or more life spheres outside of sport. When comparing mental health levels across the groups, the Dual career priority group showed a tendency for better mental health in all subscales, with significant differences compared to the Triple career priority group. These results highlight the existence of a trajectory with the triple combination of sport-studies-work, which appears to be associated with poorer mental health. Our results suggest that athletes pursuing a dual career show better mental health levels.